Dermoscopy of Cutaneous Neoplasms in Skin of Color – A Systematic Review by the International Dermoscopy Society “Imaging in Skin of Color” Task Force - Enechukwu, Nkechi Anne; Behera, Biswanath; Ding, Delaney D; Lallas, Aimilios; Chauhan, Payal; Khare, Soumil; Sławińska, Martyna; Nisa Akay, Bengu; Ankad, Balachandra S; Bhat, Yasmeen J; Kumar Jha, Abhijeet; Kaliyadan, Feroze; et al. (Dermatology Practical & Conceptual, 2023)
Over the last few decades, dermoscopy has been showed to facilitate the non-invasive diagnosis of both benign and malignant skin tumors, yet literature data mainly comes from studies on light phototypes. However, there is growing evidence that skin neoplasms may benefit from dermoscopic assessment even for skin of color. This systematic literature review evaluated published data in dark-skinned patients (dermoscopic features, used setting, pathological correlation, and level of evidence of studies), also providing a standardized and homogeneous terminology for reported dermoscopic findings. A total of 20 articles describing 46 different tumors (four melanocytic neoplasms, eight keratinocytic tumors, 15 adnexal cutaneous neoplasms, seven vascular tumors, four connective tissue tumors, and eight cystic neoplasms/others) for a total of 1724 instances were included in the analysis. Most of them showed a level of evidence of V (12 single case reports and six case series), with only two studies featuring a level of evidence of IV (case-control analysis). Additionally, this review also underlined that some neoplasms and phototypes are underrepresented in published analyses as they included only small samples and mainly certain tones of “dark skin” spectrum (especially phototype IV). Therefore, further studies considering such limitations are required for a better characterization.